2013
DOI: 10.1371/journal.pone.0084546
|View full text |Cite
|
Sign up to set email alerts
|

Increased Endothelial Inflammation, sTie-2 and Arginase Activity in Umbilical Cords Obtained from Gestational Diabetic Mothers

Abstract: ObjectiveThe aim of this study was to determine subclinical inflammation in umbilical vein derived endothelial cells (HUVECs) obtained from Asian Indian subjects with gestational diabetes (GDM) and to determine levels of angiogenic factors and arginase activity in their cord blood. MethodsThis case-control study included 38 control and 30 GDM subjects. Subjects were confirmed as GDM based on 75g oral glucose tolerance test (OGTT) conducted in the second trimester of pregnancy. Angiogenic markers and arginase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…It has been shown that the elevation of ICAM‐1 and E‐selectin could facilitate proatherogenic adhesion and recruitment of inflammatory cells across the endothelium (Epstein and Ross, ). These results show some agreement with a recent study where increased E‐selectin expression and adhesiveness of leuckocytes were observed in isolated HUVEC from GDM mothers (Giri et al, ). In contrast, their study did not show significant upregulation of ICAM‐1 expression as assessed by flow cytometry, despite increased mRNA expression.…”
Section: Discussionsupporting
confidence: 93%
“…It has been shown that the elevation of ICAM‐1 and E‐selectin could facilitate proatherogenic adhesion and recruitment of inflammatory cells across the endothelium (Epstein and Ross, ). These results show some agreement with a recent study where increased E‐selectin expression and adhesiveness of leuckocytes were observed in isolated HUVEC from GDM mothers (Giri et al, ). In contrast, their study did not show significant upregulation of ICAM‐1 expression as assessed by flow cytometry, despite increased mRNA expression.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found that differences in arginase activity between diabetic and non-diabetic mothers disappeared when controlling for the effect of the use of metformin and insulin, showing that these may affect arginase activity, similar to a finding by Kashyap et al [34]. Moreover, Giri et al found higher arginase activity in the cord blood of gestational diabetic mothers compared to their controls [35]. The offspring of mothers with normal serum glucose, presented higher levels of arginase, compared to their mothers.…”
Section: Discussionsupporting
confidence: 87%
“…The activity of carbamoyl phosphate synthase I was measured on mitochondrial extracts, isolated as previously reported [20]. Arginase activity was measured with a spectrophotometric method [21]. To measure the isocitrate dehydrogenase activity, 25 lg mitochondrial proteins was resuspended in 0.3 ml of Tris-acetate (pH 7.4), containing 5 mmol/L DL-isocitrate trisodium salt and 5 mmol/L MgCl 2 .…”
Section: Enzymatic Assaysmentioning
confidence: 99%